Eco-evolutionary Logic of Mutualisms - Chaitanya S. Gokhale; Marcus Frean; Paul B. Rainey (Dynamic Games and Applications, 2023)
Mutualistic interactions among members of different species are common, seemingly stable, and thus apparently enduring. This is at odds with standard mathematical models based solely on between-species interactions, which show mutualisms to be inherently unstable. Models incorporating parameters for punishment and reward strategies demonstrate that the range of conditions over which stability is observed can be extended; however, the role of community-level dynamics impacted by within-species interactions remains relatively unexplored. Here we develop a general and readily applicable approach for analysing a broad range of mutualisms. By incorporating within-species interactions, we show that mutualisms can be stably maintained across diverse environmental conditions without introducing changes to between-species interaction parameters. Further, a balance of within- and between-species interactions is sufficient to allow the persistence of mutualisms encountering ecological perturbations. Our simple and robust framework resonates with emerging empirical data highlighting the role of community-level interactions and population dynamics in maintaining mutualisms.
Keywords: 330; Mutualism; Evolutionary game theory; Multiple players; Population dynamics; Seasonality